Features of connections between motivation and different memory’s types - Alina Bakhvalova (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
There is the research about finding connections and correlations between scales of the test SAM (scale of academic motivation) and diagnostic results of six memory’s types – involuntary memory, voluntary memory, after-voluntary memory, short-term memory, operational memory, long- term memory in this article. The research was done with author’s test tasks that were made especially for this one study. These tasks were constructed after next famous memory’s tests of Zinchenko, Zvereva etc. The respondents of this research were 30 students and data processing was made by help of statistic computer program SPSS.